2006
DOI: 10.1161/01.res.0000202805.73038.48
|View full text |Cite
|
Sign up to set email alerts
|

The Transforming Growth Factor-β Superfamily Member Growth-Differentiation Factor-15 Protects the Heart From Ischemia/Reperfusion Injury

Abstract: Abstract-Data from the Women's Health Study show that serum levels of growth-differentiation factor-15 (GDF-15), a distant member of the transforming growth factor-␤ superfamily, are an independent risk indicator for adverse cardiovascular events. However, the cellular sources, upstream regulators, and functional effects of GDF-15 in the cardiovascular system have not been elucidated. We have identified GDF-15 by cDNA expression array analysis as a gene that is strongly upregulated by nitrosative stress in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
502
2
33

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(576 citation statements)
references
References 43 publications
24
502
2
33
Order By: Relevance
“…Circulating osteoprotegerin has been reported to be associated with cardiovascular outcomes, including mortality, MI, and incident heart failure, in several ACS cohorts 16, 17, 18, 19. However, although most of these studies include natriuretic peptides,16, 17, 19 troponins,16, 17, 18 and CRP16, 17, 18 in their adjustment strategy, none include GDF‐15, which increases in response to myocardial stress associated with inflammation and tissue damage30 and is becoming a recognized biomarker in ACS 9, 10, 14. In this large study population, the association between high osteoprotegerin levels at admission and risk of the primary end point or cardiovascular death was markedly attenuated and no longer significant after addition of NT‐proBNP, hs‐TnT, and GDF‐15 to the model that included clinical variables and inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating osteoprotegerin has been reported to be associated with cardiovascular outcomes, including mortality, MI, and incident heart failure, in several ACS cohorts 16, 17, 18, 19. However, although most of these studies include natriuretic peptides,16, 17, 19 troponins,16, 17, 18 and CRP16, 17, 18 in their adjustment strategy, none include GDF‐15, which increases in response to myocardial stress associated with inflammation and tissue damage30 and is becoming a recognized biomarker in ACS 9, 10, 14. In this large study population, the association between high osteoprotegerin levels at admission and risk of the primary end point or cardiovascular death was markedly attenuated and no longer significant after addition of NT‐proBNP, hs‐TnT, and GDF‐15 to the model that included clinical variables and inflammatory biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that GDF-15 expression significantly increases in the heart after various forms of stress, including pressure overload 22,23 . Animal studies have shown that GDF-15 promotes protective, antiapoptotic and antihypertrophic effects in the heart 23 .…”
Section: Discussionmentioning
confidence: 99%
“…W warunkach fizjologicznych ekspresja GDF-15 występuje w łożysku, prostacie, nerkach i w jelicie grubym [10]. Wyraźne nasilenie ekspresji GDF-15 z udziałem czynnika transkrypcyjnego p53 obserwuje się w makrofagach, kardiomiocytach i komórkach śródbłonka -najczęściej wskutek ich uszkodzenia, niedokrwienia lub stymulacji przez prozapalne cytokiny i reaktywne rodniki tlenowe [11][12][13] (ryc. 1) [14,15].…”
Section: Znaczenie Biologiczne Gdf-15unclassified